Simboliek in die Evangelie van Johannes - Van der Watt, J. G. (Verbum et ecclesia, 1998)
Symbolism in the Gospel according to John The use of terminology like symbol, metaphor and figurative speech is very confusing, since these terms are defined in a variety of ways. A definition of symbol is formulated, and applied to the imagery of shepherding in John 10. A few other symbols are also treated briefly to confirm the results of the symbolic analysis of shepherding in John 10.